Hubble Space Telescope Transmission Spectroscopy of the Exoplanet HD 189733b: High-altitude atmospheric haze in the optical and near-UV with STIS - Sing, D; Pont, F; Aigrain, S; Charbonneau, D; Desert, J; Gibson, N; Gilliland, R; Hayek, W; Henry, G; Knutson, H; Etangs, A; Mazeh, T; et al. (2011)
We present Hubble Space Telescope optical and near-ultraviolet transmission spectra of the transiting hot-Jupiter HD189733b, taken with the repaired Space Telescope Imaging Spectrograph (STIS) instrument. The resulting spectra cover the range 2900-5700 Ang and reach per-exposure signal-to-noise levels greater than 11,000 within a 500 Ang bandwidth. We used time series spectra obtained during two transit events to determine the wavelength dependance of the planetary radius and measure the exoplanet's atmospheric transmission spectrum for the first time over this wavelength range. Our measurements, in conjunction with existing HST spectra, now provide a broadband transmission spectrum covering the full optical regime. The STIS data also shows unambiguous evidence of a large occulted stellar spot during one of our transit events, which we use to place constraints on the characteristics of the K dwarf's stellar spots, estimating spot temperatures around Teff~4250 K. With contemporaneous ground-based photometric monitoring of the stellar variability, we also measure the correlation between the stellar activity level and transit-measured planet-to-star radius contrast, which is in good agreement with predictions. We find a planetary transmission spectrum in good agreement with that of Rayleigh scattering from a high-altitude atmospheric haze as previously found from HST ACS camera. The high-altitude haze is now found to cover the entire optical regime and is well characterised by Rayleigh scattering. These findings suggest that haze may be a globally dominant atmospheric feature of the planet which would result in a high optical albedo at shorter optical wavelengths.